Simulation of Micristrip Patch Antenna with Truncated Corners - Kanniga, E.; Sindhuja, S. (International Journal of Psychosocial Rehabilitation, 2019)
In the last few years the Global Positioning System (GPS) has been used in a variety of applications for which new and more restrictive requirements in the design of the receiving antenna have been introduced .In particular, for high precision GPS application, such as differential GPS, GPS-based space graft altitude determination or geodetic surveying, receiving antenna with superior rejection to multipath signals is required. Multipath arises when the GPS transmitted signal takes different paths to receiving antenna and being the signals from these paths added with different spaces, this result in a significant amplitude and phase distortion.